Prognostic Value of MiR-21: An Updated Meta-Analysis in Head and Neck Squamous Cell Carcinoma (HNSCC) - Irimie-Aghiorghiesei, Alexandra Iulia; Pop-Bica, Cecilia; Pintea, Sebastian; Braicu, Cornelia; Cojocneanu, Roxana; Zimța, Alina-Andreea; Gulei, Diana; Slabý, Ondřej; Berindan-Neagoe, Ioana (Journal of clinical medicine, 2019)
Head and neck squamous cell carcinoma (HNSCC) is a group of malignancies with serious impact on patient quality of life due to a reduced rate of response to chemotherapy or radiation therapy. MiR-21 has been identified as one of the most common proto-oncogenes. It is hypothesized that upregulated miR-21 could serve as a potential biomarker for human cancer diagnosis. Considering the target genes identified for miR-21 in HNSCC, this transcript is an important player in several cellular processes that control carcinogenesis. The abnormal expression of miR-21 in this group of pathologies has been assessed in several publications, but given the heterogeneity of the published results, a meta-analysis and proper bioinformatics analysis of expression databases are needed to correctly establish the prognostic potential of this molecule. The present meta-analysis comprises the published survival data on HNSCC patients, reported as HR and 95% CI, in association with the expression levels of miR-21. Our investigation revealed that miR-21 could be used successfully as a prognostic biomarker in HNSCC patients, confirming its oncogenic potential. Specifically, the upregulation of miR-21 in these patients predicts a worse outcome in terms of survival rate.
Keywords: head and neck cancer; miR-21; bioinformatics analysis; survival; prognostic